PENERAPAN EVIDENCE BASED NURSING PENGARUH TERAPI BACK MASSAGE TERHADAP KUALITAS TIDUR PASIEN DI RUANG ICU RSUD TARAKAN - Shania Hasina Sidiki, (2022)
Sleep is an important role in improving health, recovery and overcoming illness among patients in the ICU, but critical patients who are treated in the intensive care unit (ICU), sleep becomes difficult because of several disturbance. Disturbances that can occur in the ICU such as noise levels (monitor alarms, conversations between nurses), lighting levels, nursing activities (monitor vital signs). Improving sleep quality of patient is one of the nurse's duties in nursing care. One of the non-pharmacological therapies that can be given is back massage therapy. This study aims to determine the application of back massage therapy to the sleep quality of patients in the ICU. Patient sleep quality was measured using the Verran and Snyder Halpern Sleep Scale (VSH) questionnaire. The results obtained after back massage therapy for 10 minutes in 3 days an increase in the sleep quality of patients. It is hoped that back massage therapy can be applied to ICU patients to improve sleep quality.